Diversification of the Healthy Life Expectancy (HLE) and the Factors Affecting It - Ucieklak-Jeż, Paulina (Dywersyfikacja oczekiwanej długości zdrowego życia i czynniki ją określające, 2009)
Healthy Life Expectancy (HLE) is one of fundamental indexes of the assessment of the state of health of the population. The aim of this article is to answer how HLE depends on economic development. The increase of welfare implies the existence of good living conditions influencing longer HLE estimation of the studied population. A graph of the value of the HLE in relation to health expenditure has been plotted. The relationship between them is consistent with the view that health expenditure has diminishing returns. The relationship is positive up to a certain expenditure level per capita. Additional expenditure beyond this level has a negligible incremental effect on the HLE.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 66, s. 102-119